PO.7.155 Study of the comorbidities present in the patients included in the registry of systemic lupus erythematosus of the spanish society of rheumatology (relesser). (27th September 2022) - Lois-Iglesias, A; Iñigo, R; Galindo Izquierdo, M; Calvo-Alén, J; Balboa-Barreiro, V; Mouriño, C; Olivé, A; Melero, R; Fernández-Nebro, A; Andrés, M; Erausquin, C; Tomero, E; et al.
Abstract : Background: The survival of patients with systemic lupus erythematosus (SLE) has increased in recent years, but they have higher morbidity and mortality than the general population. Purpose: To study the prevalence of comorbidities in patients with SLE and its relationship with damage, gender and treatments received. Methods: Cross-sectional multicenter descriptive study of a cohort of adult patients with SLE. Results: We studied 3, 656 patients, 90.3% women, mean age (±SD) at diagnosis of 35.2(±14.7) years and duration of SLE of 142.6(±100.8) months. We analyzed 27 comorbidities. 79.73% of the patients presented any, with the maximum accumulated being 14. The most frequent were smoking, dyslipidemia and arterial hypertension. 38.05% of patients accumulated damage. Males accumulated more comorbidities (85.48% vs. 79.1%, p=0.003) and damage (47.03% vs. 37.11%, p<0.001). The first criterion for SLE appeared at a younger age in patients who did not have comorbidities: 27.73(±12.04) years vs. 34.47(±14.76) years; p<0.001. We found that there is a positive correlation between the number of comorbidities and the number of systems with damage (Spearman's Rho = 0.478, p<0.001). There is a positive correlation between the number of comorbidities and damaged systems with the number of hospitalizations by disease activity (Rho=0.265 and 0.396 respectively, p<0.001 in both contrasts) as well as with the number of serious infections (Rho=0.299 and 0.307 respectively, p <0.001 in both contrasts). We found more patients without comorbidities in those who did not receive glucocorticoids (9.94% vs. 15.48%, p<0.001) and more patients with comorbidities in those who did not receive antimalarials (89.1% vs. 81.78%, p<0.001). There were significant differences in the presence of comorbidities in those treated with cyclophosphamide, mycophenolate, azathioprine or rituximab. Conclusions: A high percentage of patients with SLE have comorbidities. With few exceptions, they are more frequent in males. The onset of SLE was later in patients with more comorbidities. We found variations in comorbidities depending on the treatments received.